Features of explication "Practice": : Between Ukrainian Soviet and Chinese Marxism - Rudenko, Sergii; Turenko, Vitalii; Nelipa, Dmytro; Zarutska, Olena; Omelchenko, Victoria (Kalágatos, 2023)
The article carries out a comprehensive comparative analysis of the understanding of "practice" in the context of thinkers of two directions of Marxism – Ukrainian-Soviet and Chinese philosophers. When examining the concept of "practice" in Ukrainian Soviet Marxism, the work of the following domestic thinkers is studied: P. Kopnin, V. Shynkaruk, V. Tabachkovskyi, V. Ivanov, O. Yatsenko. It is substantiated that domestic thinkers in the 60s and 80s of the XX century. focused their attention on practice not so much in the epistemological or socio-philosophical content, but in the anthropological and existential one. According to most of them, practice is not so much the opposite of theory, but a fundamental principle of consideration of all scientific and theoretical problems through the prism of their humanistic content, which allows us to realize the connection of theoretical knowledge with all the variety of ways of mastering a person. being, reveals the essence of knowledge as a cultural phenomenon. The work "On Practice" by Mao Zedong is analyzed, which reveals the prospect of further understanding of the researched concept within the framework of Chinese Marxism. In particular, he singles out two key aspects of the explanation of "practice": epistemological and political-philosophical. Therefore, Marxism in China is used to solve its problems and transform the rich practical experience of the state into theory, as well as in combination with Chinese history and unique Chinese traditional culture.